Intimacy - Kureishi, Hanif, 1954- (Faber & Faber, 2000)
A novel by the author of "The Buddha of Suburbia" and "My Beautiful Laundrette" which analyzes the agonies and joys of being connected to another person. Jay, who is leaving his partner and their two sons, reflects on the vicissitudes of his relationship with Susan.